A Randomized Dose-Escalation Study of the Safety and Anti-Inflammatory Activity of the p38 Mitogen-Activated Protein Kinase Inhibitor Dilmapimod in Severe Trauma Subjects at Risk for Acute Respiratory Distress Syndrome. Issue 9 (September 2015) - Christie, Jason D.; Vaslef, Steven; Chang, Philip K.; May, Addison K.; Gunn, Scott R.; Yang, Shuying; Hardes, Kelly; Kahl, Lesley; Powley, William M.; Lipson, David A.; Bayliffe, Andrew I.; Lazaar, Aili L.
<x xml:space="preserve">Abstract</x> Objectives: There are no current pharmacological therapies for the prevention or treatment of acute respiratory distress syndrome. Early dysregulated inflammation likely plays a role in acute respiratory distress syndrome development and possibly acute respiratory distress syndrome outcomes. p38 mitogen-activated protein kinase is central to the regulation of multiple inflammatory mediators implicated in acute organ dysfunction and is the target for a novel class of cytokine-suppressive anti-inflammatory drugs. In preclinical models, p38 inhibitors reduce lung injury following pancreatitis and burn injury. Design: We conducted a phase IIa, randomized, double-blind, placebo-controlled, parallel-group study to evaluate the safety and tolerability of dilmapimod, a novel p38 mitogen-activated protein kinase inhibitor, in patients at risk for developing acute respiratory distress syndrome admitted with an Injury Severity Score more than 16, excluding head trauma. Enrolled patients received 4- or 24-hour IV dilmapimod infusions at different doses or placebo, daily for 3 days, in four separate cohorts. Setting: Multicenter randomized clinical trial of large, academic trauma centers. Measurements and Main Results: Seventy-seven patients were enrolled. Although adverse events were common in this critically ill population, dilmapimod was well tolerated, with no clinically relevant safety findings. Pharmacokinetic models indicated that the higher dose of 10 mg given as continuous infusion over 24 hours had the most favorable plasma concentration profile. Likewise, measures of soluble inflammatory markers including interleukin-6, C-reactive peptide, interleukin-8, and soluble tumor necrosis factor receptor 1 were most different between this dosing arm and placebo. Although the study was not specifically designed with acute respiratory distress syndrome as an outcome, the number of patients who developed acute respiratory distress syndrome was small (2/77). Conclusions: The novel p38 mitogen-activated protein kinase inhibitor dilmapimod appears well tolerated and may merit further evaluation for prevention of acute respiratory distress syndrome and other organ injury in larger clinical trials. Furthermore, results of this early-phase trial may aid in design of future studies aimed at prevention of acute respiratory distress syndrome and other organ injury.